Impact of artificial intelligence on business models in industry 4.0. bibliometric analysis and systematic review of the literature - Torres, Victor Yesid Sotelo; Rodelo, Alexander Rodriguez; Julio, Rosa Carolina Cittelly; Lievano, Jhony Alexander Barrera (Edelweiss Applied Science and Technology, 2025)
Industry 4.0 represents a paradigm shift in the business and industrial sectors, where the integration of digital and physical technologies transforms how companies operate, conduct business, create value, and interact with their customers in an increasingly automated and digitized world. Despite its technological advancements, Industry 4.0 faces significant challenges, such as resistance to change, the need for adequate technological infrastructure, and the demand for skilled personnel. This article analyzes the impact of artificial intelligence on business models within Industry 4.0, focusing on research conducted between 2018 and 2023 obtained from the Scopus database. The primary question addressed is: What specific impact does artificial intelligence have on the business models of companies in Industry 4.0? To answer this, a systematic literature review was conducted. The study concludes that AI enhances efficiency in companies, playing a significant role in decision-making, innovation, and sustainability, which are critical elements of the business models in Industry 4.0.